2018
DOI: 10.1159/000494467
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of KIF2A is Suppressed by miR-206 and Associated with Poor Prognosis in Ovarian Cancer

Abstract: Background/Aims: This study aimed to investigate the expression and prognostic value of kinesin family member 2A (KIF2A) and the suppression effects of microRNA-206 (miR-206) on KIF2A in ovarian cancer. Methods: Ovarian cancer tissues from patients and ovarian cancer cell lines (A2780 and SKOV3) were used in this study. miR-206 mimics and control were transiently transfected into cells. RT-qPCR was performed to detect KIF2A mRNA and miR-206 expression levels, Western blot was performed to detect KIF2A protein … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
53
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 48 publications
(54 citation statements)
references
References 32 publications
1
53
0
Order By: Relevance
“…The KIF gene family, which encodes proteins, is involved in many important physiological processes, especially intracellular transport, chromosome separation, mitotic spindle formation and cytokinesis. Some studies have suggested that mutations in the KIF gene family are involved in the formation of many cancers (Sheng et al, 2018;Xia et al, 2018;Xie et al, 2018). There are few studies on KIF18b and LUAD, and only confirmed that LUAD patients with high KIF18b expression have a poor prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…The KIF gene family, which encodes proteins, is involved in many important physiological processes, especially intracellular transport, chromosome separation, mitotic spindle formation and cytokinesis. Some studies have suggested that mutations in the KIF gene family are involved in the formation of many cancers (Sheng et al, 2018;Xia et al, 2018;Xie et al, 2018). There are few studies on KIF18b and LUAD, and only confirmed that LUAD patients with high KIF18b expression have a poor prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…KIF14 promotes tumor progression and is associated with poor prognosis in gastric cancer (Yang et al, ). KIF2A is suppressed by a micro RNA, miR‐206 and correlated with the poor prognosis in ovarian cancer (Sheng et al, ). These finds, together with our results in this study, indicated the key function of kinesin family in cancer development.…”
Section: Discussionmentioning
confidence: 99%
“…The kinesin proteins are microtubules depolymerases, which are involved in mitosis, cell migration, trafficking, and cell signaling . KIF2A, as one member of the kinesin protein family, has attracted a lot of attention due to its implication in the development and progression of several tumors . For example, in gastric cancer, KIF2A is upregulated in cancerous tissues compared with adjacent non‐tumor tissues and its high expression is correlated with advanced TNM stage and LYN metastasis .…”
Section: Discussionmentioning
confidence: 99%
“…The predictive value of KIF2A in prognosis is reported in several tumors . One study exhibits a correlation between KIF2A expression and the 5‐year survival rate in patients with gastric cancer .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation